PENGARUH DESENTRALISASI FISKAL TERHADAP PENGALOKASIAN BELANJA MODAL DI KABUPATEN DAN KOTA NUSA TENGGARA BARAT - Assyifa, Baiq Siti Ainaya; Muttaqin, Aminullah Achmad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to determine the effect of fiscal decentralization on capital expenditure in the Districts and Cities of West Nusa Teggara in the period of 2011-2021. In this study, fiscal decentralization is represented by Original Regional Revenue (ORR), General Allocation Fund (GAF), Special Allocation Fund (SAF), and Reveneu Sharing Fund (RSF). The resources of data used are budget realization report of 10 Regency/City Regional Government Province of West Nusa Tenggara that was published at the Directorate General of Financial Balance Ministry of Finance. The type of research is quantitative. Data analysis using panel data regression analysis which is used the combination period/years of 2011-2021 time series data and used the crosssection data of 10 Regency/City Regional Governments in Province of West Nusa Tenggara. The results of the study show that Original Regional Revenue (ORR) has a insignificant effect on capital expenditure. General Allocation Fund (GAF) has positive and significant effect capital expenditure. Reveneu Sharing Fund (RSF) has a positive and significant effect on capital expenditures. Special Allocation Fund (SAF) has a positive and significant effect on capital expenditures.